The Fourteenth Amendment and the fight for equality - Bajramovic, Hana (Bajramovic, Hana. Whose right is it., 2024)
"The Fourteenth Amendment to the U.S. Constitution, known as the "equality amendment," was passed in 1868 during the time after the Civil War to help protect the rights and freedoms of Black Americans. In the centuries that followed, the amendment grew to protect the rights of women, immigrants, and LGBTQ+ people as well. But in recent years, the scope of the Fourteenth Amendment has shifted dramatically. A series of landmark Supreme Court cases-- ranging from abortion to affirmative action-- have rolled back the amendment's guarantees and called into question its usefulness as a tool in the fight for equality. What does the future hold for the Fourteenth? It explores how one amendment to the Constitution shaped civil rights and liberties in America and became the focus for many of today's most important political debates. Featuring historical photos and informative graphics, this book shows a new generation of activists what the fight for equality across race, sexuality, gender, and citizenship might look like in the years to come."--